Staples and the Development of the Capitalist Mode of Production: A Study of Mining in Canada 1845-1920 - Moore, Phillip William (My University, 1978)
A substantial amount of writing in Canadian Political Economy has emphasized the colonial/dependency relationship of Canada to Europe and the United States. The development of Canada has, in this schema, been viewed as a product of international systems of trade in raw materials and finished goods, such that the character of a given society, the type of social relations, its "state" of development, etc., are determined by the peculiar nature of the product(s) (staples) being traded. The theory shares, in essence, a number of similarities with those of mercantilism, by stressing the relationship between trade and wealth with respect to the development of society. In this thesis the question of staple production is approached in a somewhat different fashion; focussing on mining as a specific case of study. The development of mining in Canada is dealt with in relation to two basic concepts: (1) modes of production, including the process of transtion, and (2) the process of capital accumulation on a world scale. This development is viewed as being associated with the Canadian Industrial Revolution, with emphasis on the changing and developing relations between producers and non-producers interacting with the corresponding level of technological development. Under such circumstances the Industrial Revolution, as well as involving an increasing application of machinery, involved fundamental transformations of the relations between producers so that changes at the level of the organization of production occurred, both with respect to the possession of mines, and the actual organization of the labour force in mining. Further, in the discussion, the Industrial Revolution within Canada linked also to the developing international capitalist system. It is argued that the peculiar character of the development of mining in Canada was conditioned by the expansion of the capitalist mode of production, not only within national boundaries, but as a process of accumulation increasingly on an international level.
Keywords: Sociology; Sociology